Don Lamberton: a view from the periphery. (1st December 2015) - Doessel, D.P.
Abstract : It is sometimes said that Don Lamberton was weak on 'standard' microeconomic theory. This was not my experience: he introduced me to some important theoretical developments in the discipline of economics. In my academic career, I have undertaken various studies on issues that interest me, studies which have been influenced by literature brought to my attention by Don Lamberton. My perspective on Don Lamberton is that of, not exactly an outsider, but someone not in the inner circle: my position in the Lambertonian landscape was on the periphery. The paper concludes with some reflections on two issues outside economics.